Pengelolaan Dana Desa Di Tinjau Dari Perspektif Pencegahan Korupsi - Roy Marthen Moonti (Universitas Borneo Tarakan, 2020)
The research aims at investigating the prevention efforts of corruption crime of management village fund reviewed from Indonesian law and to investigate the village fund management model reviewed from the perspective of corruption prevention aspect. This research used normativeempirical, the data used primary and secondary data from questionnaires and interview. This research is analyzed in qualitative with inductive method, and descriptive which is explaining, and describe appropriate with problems related with this research. In prevent corruption happens in management village fund, the effort which is offered by the researcher is: identified corruption modus, the increase ofintegrity capacityvillage officials, increase the capacity of village facilitators, refused intervention from local government in order to prevent the fraud in managing village funds and model village funds management of all village refers to Minister of Home Affairs regulation number 20 year of 2018 changes to the Minister of Home Affairs regulation number 113 year of 2014 which clearly there are all governance of village fund management models that are right on target, but in managing the village fund is still has officials not maximum or patient in manage village fund.Suggestion which is offered from the researcher in prevent corruption are identifycorruption modus, the increase ofintegrity capacity village officials, increase the capacity of village facilitators, refused intervention from local government, and T test result showed that the efforts of corruption prevention is effective and influence in management of village fund.